Desenvolvimento de um sistema de aquisição de dados e monitoramento para o diagnóstico de centrais de geração fotovoltaica - Treter, Marcos Eduardo (2016)
This master thesis presents a data acquisition and monitoring system for photovoltaic solar generation plants. The energy produced by photovoltaic systems depends on several factors, such as: array settings, weather conditions, shading, failures, among others. Due to the influences of solar irradiance and temperature on power generation, it is difficult to evaluate the operation of PV systems. This paper proposes a method to detect periods in which the photovoltaic system is inappropriate behavior, that is, periods in which the energy production is lower than expected. A data acquisition system was developed for photovoltaic applications, with the following characteristics: cloud data storage, data acquisition rate of 1 second and possibility of communicating using different communication protocols and physical interfaces. To detect inappropriate behaviors in the PV system was proposed an algorithm that performs the comparison between the estimated power by a mathematical model and the power measured by the data acquisition system. If the difference between the measured power and the estimated power exceeds a predetermined constant, it appears that the photovoltaic system is inappropriate operation, that is, with energy production lower than expected. The method for detecting the type of problem detected if the system is operating under sunny or overcast sky conditions condition, and take different decisions depending on the condition. The methods developed in the master thesis were tested experimentally, and the results were satisfactory to detect the main inappropriate behavior of PV systems.